Comparing Condom Use With Different Types of Partners Evidence From National HIV Surveys in Africa - de Walque, Damien (The World Bank, 2009)
Based on nationally representative samples from 13 Sub-Saharan African countries, this paper reinforces and expands previous findings that condom use in general is low in this region, men report using condoms more frequently than women, and unmarried individuals report they use condoms more frequently than married individuals with their spouse. Based on descriptive, bivariate, and multivariate analyses, the authors also demonstrate to a degree not previously shown in the current literature that married men from most countries report using condoms with extramarital partners about as frequently as unmarried men. However, married women from most countries included use condoms with extramarital partners less frequently than unmarried women. This result is especially troubling because marriage usually ensures regular sexual intercourse, providing more opportunities to pass HIV from extramarital partner to spouse than an unmarried person who may also have multiple partners but not as regular sexual intercourse